Pengaruh Pengeluaran Pemerintah dan Investasi terhadap Pertumbuhan Ekonomi di Provinsi Jambi Tahun 2004-2023 - Hasminidiarty, Hasminidiarty; Putriyani, Sri Devi (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
This research aims to determine the effect of government spending and investment on economic growth in Jambi Province during the 2004-2023 period. Data obtained from the Central Statistics Agency (BPS) of Jambi Province. This research uses multiple linear regression analysis tools. The results of this research show that simultaneously there is a positive and significant influence between government spending and investment on economic growth, but partially the investment variable does not show a significant influence on the economic growth of Jambi Province during the 2004-2023 period.